Design, Synthesis and in vitro Controlled Release of New Adamantanodiarylketone Antimycobacterials. Issue 37 (1st October 2019) - Vlachou, Marilena; Papanastasiou, Ioannis P.; Georgiadis, Markos‐Orestis; Tsakoumagkou, Argyro; Siskos, Zacharias; Siamidi, Angeliki; Konstantinou, Anna; Vocat, Anthony; Cole, Stewart T.
Abstract: In the present investigation, the synthesis, the biology and the development of matrix tablet formulations for the in vitro controlled release of new adamantane diarylketone antimycobacterial derivatives, is presented. In the skeleton of the new compounds, a diarylketone, functionalized by a 2‐hydroxypropylenoxy‐3‐butylamine, a 2‐hydroxypropylenoxy‐3‐hexylamine and a 1‐(2‐hydroxyoctyl)piperidin‐4‐yl moiety, is incorporated at the C‐1 adamantane position. The new derivatives were tested against the H37Rv Mycobacterium tuberculosis strain and exhibited satisfactory activity. In view of their lipophilic character, it was intriguing to examine their in vitro dissolution profile in buffer solutions simulating the gastric and intestinal environments. To this end, matrix tablets of the most active compound, {4‐[(adamantan‐1‐yl)phenyl‐4‐(3‐(butylamino)‐2‐hydroxypropoxy)]phenyl}methanone (A ), incorporating the appropriate excipients, were prepared using the direct compression method. The preliminary test results show that its dissolution profile is in alignment with the desired pattern for the per os administration of tuberculocidal agents. Abstract : Three new adamantane‐based diarylketone compounds A‐C were prepared and tested for their antimycobacterial action. The 2‐hydroxypropylenoxy‐3‐butylamine substituted analogue A had a noteworthy antitubercular activity and although quite lipophilic showed a controlled release profile, in aqueous media simulating the gastrointestinal environment, which is in alignment with the desired pattern for the per os administration of tuberculocidal agents.